Quick determination of actual oil content in oil palm fruit bunch using near infra red (NIR) scanning spectrometer - Nurul Aslah, Ismail (2010)

(untitled)
This research was being carried out to determine the oil contents of oil palm fruits in fastest possible time and to determine the effects of bunch weight (ranges from <20kg, 20-29kg, 30-39kg, 40-49kg and 50-59kg) and palm tree ages (ranges from 812years, 13-20years and >21years) on oil contents of oil palm fruits. The oil contents were determined using conventional method and the Near Infrared Spectrometer (NIRS). The other objective of this research is to improve the quality of the incoming fresh fruit bunch into Palm Oil Mill. The recent problem in the industry is to resolve the oil content dispute between the oil mill owners and fruit owners in fastest possible time, in order for both parties to directly determine the price based on the actual percentage of oil contents in the oil palm fruits. For the parameters that have been studied, by using the conventional methods, the results shown that the bunch weight of 30-39kg and the tree ages of 8-12 years old have the highest oil contents. Therefore, by using the Near Infrared Spectrometer, it will be used to provide faster and reliable results and it will be expected to replace the conventional methods as it has potential to reduce time and energy-consuming in years to come. In the future, the oil palm mills will only have to pay the right price for the right quality of the oil palm fruits.